DAMPAK PENETAPAN HARGA ECERAN TERTINGGI TERHADAP HARGA DAN KETERSEDIAAN BERAS DI TINGKAT PEDAGANG PASAR TRADISIONAL SUMATERA SELATAN - Thirtawati Thirtawati; Desy Aryani; Marwan Sufri (University of Jember, 2019)
Highest Retail Price (HRP) of rice is a price policy implemented by the government to maintain price stability, certainty, and affordability so there is no excessive increase. This study analyzes how traders apply and understand the HRP; analyzes changes in price, quality, trademark, volume of buying and selling rice at the trader level in traditional markets and how the effectiveness of HRP determination of medium and premium rice. Research respondents were 12 traditional market rice traders from four regions in South Sumatra, namely Palembang City and Prabumulih representing consumer regions and OKI and Muara Enim Regencies representing producer regions. The results showed that not all traders knew and agreed with the policy of HRP determination. Determination of HRP causes a change in the price and quality of rice sold where the proportion of premium rice sales becomes greater than before, while for trademarks there is no change, but there is additional information of the type of rice (medium or premium) on rice packaging. Based on the calculation results, it appears that the average effectiveness of medium rice is 1,028 after the determination of HRP so that it is considered ineffective, while the average effectiveness of premium rice is 0.920 (effective).